Gracilechinus alexandri - Madeira, Patrícia; Kroh, Andreas; Cordeiro, Ricardo; De, António M.; Martins, Frias; Ávila, Sérgio P. (Zenodo, 2019)
Gracilechinus alexandri (Danielssen & Koren, 1883) Reports for the Azores: Echinus alexandri Danielssen & Koren, 1883 — $ Koehler 1895b: 229, 1909: 230; Mortensen 1927a: 304–305, figs. 167.1, 172– 173, 1943a: 65–68, figs. 20a, 21a–b, pl. 11, figs. 8–11; Grieg 1932: 42; Gage et al . 1985: 184; Serafy & Fell 1985: 4, 20, 21–22, fig. 29;? $ Pérès 1992: 255; García-Diez et al . 2005: 50 $ Desbruyères et al . 2006: 479, figs. 1–4; Gracilechinus alexandri (Danielssen et Koren, 1883) — Mironov 2014: 123–124. Type locality: off Lofoten (69°18’N, 14°32’E), Norway. See: Danielssen & Koren (1883: 294–296, pl. 3–4, figs. 7–16; as Echinus alexandri ); Mortensen (1903: 146– 150, pl. 5, figs. 2, 3, 5,7, pl. 15, figs. 13, 17, pl. 16, fig. 8, pl. 17, figs. 9, 11, 19, 23, 25, pl. 19, figs. 16, 31, 34, 38, pl. 20, figs. 1, 2, 27, pl. 21, figs. 18–20, 27; 1943a); Desbruyères et al . (2006). Occurrence: North Atlantic, in the west, along the east side of North America (Serafy & Fell 1985) and in the east from Icelandic, Scandinavian and British deep waters (Mortensen 1903, 1927a), southwards to the Bay of Biscay and the Azores (Koehler 1909); possibly also in Tristan da Cunha (Mortensen 1943a). Depth: 230– 3,150 m (Desbruyères et al . 2006); AZO: 1,165 –1,940 (?2,560) m (Koehler 1909, Pérès 1992). Habitat: soft substrates, ooze to sand (Koehler 1909, Gage et al . 1985); diet consisting of bottom mud with foraminiferans (Serafy & Fell 1985); feeds also on deep-sea reef building corals such as Lophelia pertusa and Madrepora oculata (Stevenson & Rocha 2012); can be found in the vicinity of deep-water hydrothermal vents (Desbruyères et al . 2006). Larval stage: planktotrophic (Emlet 1995). Remarks: Koehler (1898) examined young specimens collected by Hirondelle in Azorean waters between 1,372 and 1,850 m, which he identified as possible Gracilechinus acutus (= Echinus acutus ) or Gracilechinus alexandri (= Echinus alexandri ) but due to the small size of the animals (less than 1 cm) he could not ascertain ...